Theoretical perspectives on preventing fishing vessel accidents. - Roger Boshier (Adult Education Research Conference, 1997)
Despite the availability of new technologies, fishing vessels come to grief far too often. Prevention education is excessively functionalist and not sufficiently focused on human factors. The author interrogates the problem from contrasting theoretical perspectives and claims prevention educators should embrace subjective as well as objectivist ontologies and place power relations at the centre, not on the margins, of their efforts.